Enhanced extensive reading in EFL classroom: An investigation of its effect on learners’ incidental preposition acquisition - Simamora, Anggi Milfa nersya; Benni Ichsanda Rahman (Wacana: Jurnal Penelitian Bahasa, Sastra dan Pengajaran, 2024)
This study investigates the impact of enhanced extensive reading on the incidental acquisition of prepositions "in," "on," and "at" related to time and place among English as a Foreign Language (EFL) learners. Ten senior students from the English Education Department at the State Islamic University of North Sumatera participated in a pre-experimental design with a one-group pretest-posttest approach. The pretest assessed preposition proficiency, followed by a two-week extensive reading intervention, resulting in a significant improvement in post-test scores, as evidenced by a paired t-test (p = .000). Utilizing Google Forms for standardized data collection, the study incorporated multiple-choice and fixing incorrect prepositions sections, revealing a notable mean score increase from 59.5 to 69 post-intervention. Effect sizes, calculated with Cohen's D, indicated a small effect (0.15) in the multiple-choice section and a substantial effect (0.78) in fixing incorrect prepositions. Participants' positive perception of extensive reading aligns with literature emphasizing the benefits of repeated exposure to prepositions in texts. Acknowledging limitations such as a small sample size and limited reading materials, the study recommends future research to enhance study design and diversify participants. Common mistakes in preposition usage, including challenges in time-specific contexts and confusion between "in," "on," and "at," were analyzed, emphasizing the importance of targeted instruction. In conclusion, combining incidental learning through enhanced extensive reading with targeted instruction proves effective in improving EFL learners' incidental acquisition of English prepositions, offering valuable insights for educators to address specific challenges in preposition usage.